Contrasting features of childhood and adolescent melanomas. Issue 3 (23rd March 2018) - Bartenstein, Diana W.; Kelleher, Cassandra M.; Friedmann, Alison M.; Duncan, Lyn M.; Tsao, Hensin; Sober, Arthur J.; Hawryluk, Elena B.
Abstract: Background/Objectives: Melanoma in children and adolescents is uncommon, and there are limited data on pediatric outcomes. Several studies have shown comparable survival rates in children and adults, but other research demonstrates that prepubescent children have more favorable outcomes. This study aims to compare childhood and adolescent melanoma. Methods: Retrospective cohort study of children who received a melanoma diagnosis at the Massachusetts General Hospital between January 1, 1995, and December 21, 2016. Childhood melanoma is defined as disease occurring in patients younger than 11 years old, and adolescent melanoma is defined as disease occurring in patients 11 to 19 years old. Patients diagnosed with ocular melanoma and borderline tumors of uncertain malignant potential were excluded. This analysis compares clinical, histopathologic, and outcome characteristics of childhood and adolescent melanoma. Results: Thirty‐two children with melanoma were identified (12 children, 20 adolescents). The spitzoid melanoma subtype was significantly more common in children (6/12) than adolescents (2/20) ( P  = .01). Four adolescents and no children with melanoma died from melanoma, and survival was significantly different between the age groups ( P  = .04). Median follow‐up time for survivors was 3.6 years. Conclusions: These results suggest that children and adolescents present with different melanoma subtypes and that adolescents have a more aggressive disease course than children.